Rifoligotyping assay: an alternative method for rapid detection of rifampicin resistance in Mycobacterium tuberculosis isolates from Morocco - Chaoui, Imane (Biotechnol Biotechnol Equip, 2014)
One of the greatest threats to global tuberculosis (TB) control is the growing prevalence of drug resistant strains. In the past decades, considerable efforts have been made upon the development of new molecular technologies and methodologies for detection of drug resistance in Mycobacterium tuberculosis (MTB). A sensitive, specific reverse line blot assay, called rifoligotyping (RIFO), for the detection of genotypic resistance to rifampicin (RIF), was designed and evaluated. RIFO includes oligonucleotide probes specific for wild-type and mutant sequences, allowing specific and sensitive detection of both genotypes in a single assay. The RIFO was applied on 500 MTB isolates from Morocco. The results of the RIFO showed a good sensitivity (90.9%) and high specificity (100%); the positive and negative predictive values were 100% and 96.1%, respectively. This rapid, simple, economical assay provides a practical alternative for RIF genotyping, especially in low-income countries, to improve TB control and management.